A review of the effects of alkali and alkaline earth metal species on biomass gasification - Yu, Junqin; Guo, Qinghua; Gong, Yan; Ding, Lu; Wang, Jiajian; Yu, Guangsuo (Fuel processing technology, 2021)
The effects of alkali and alkaline earth metals (AAEM) on the component and distribution of products, gasification reactivity, catalytic mechanism and char-ash/slag transition during biomass gasification were reviewed. Biomass is mainly composed of cellulose, hemicellulose and lignin, and has a much higher AAEM species content than coal. The influence of inherent AAEM on biomass gasification is closely related to the gasification agent and operating conditions. To remove tar and reduce soot, interest has grown on the subject of AAEM catalysis for biomass gasification. Therefore, component and distribution of products and gasification reactivity in inherent and loaded AAEM catalytic biomass gasification were reviewed. Furthermore, the effects of AAEM on biomass conversion can be divided into homogeneous and heterogeneous catalytic effects based on the phase states involved in chemical reactions. Three main mechanisms including oxygen transfer mechanism, active site mechanism and catalytic desorption mechanism are summarized to understand the heterogeneous catalytic process. The attribution to the promotion of the homogeneous reaction is concluded as the volatile gaseous AAEM catalyzed the water-gas shift reaction and the hydrocarbon reforming reaction. In addition, the effects of AAEM content on char-ash/slag transition in biomass gasification were also reviewed. •Biomass component gasification characteristics are summarized and compared.•Product distribution and reactivity of biomass gasification are reviewed.•Three main AAEM catalytic biomass gasification mechanisms are summarized.•Effect of AAEM on char-ash/slag transition during gasification is discussed.